Radiative parameters of high-lying levels in neutral rhodium. Issue 4 (17th March 2021) - Li, Yongfan; Geng, Yidan; Liu, Meina; Ma, Huiting; Wu, Yaxin; Zhang, Lijun; Gamrath, Sébastien; Quinet, Pascal; Dai, Zhenwen
ABSTRACT: Radiative lifetimes of 20 high-lying excited levels in neutral rhodium (Rh i ) were measured using time-resolved laser-induced fluorescence technique, 17 of which are reported for the first time to our knowledge. These lifetimes were combined with theoretical branching fractions obtained from pseudo-relativistic Hartree–Fock calculations to deduce semi-empirical transition probabilities and oscillator strengths for 63 Rh i spectral lines.